Using a wireless consumer accelerometer to measure tibial acceleration during running: agreement with a skin-mounted sensor - Brayne, L.; Barnes, A.; Heller, B.; Wheat, J. (Sports Engineering, 2018)
Real-time monitoring and feedback of tibial acceleration using wireless skin mounted sensors may reduce the risk of tibial stress fractures in runners. The purpose of this study was to assess the agreement between a wireless accelerometer and a gold standard reference accelerometer, both skin mounted, in measuring peak axial tibial acceleration when treadmill running at a range of speeds. A research grade accelerometer was mounted to a wireless accelerometer and attached to the tibia. Peak positive tibial accelerations of 13 participants were compared at 2.5, 3.5 and 4.5 m s^-1. Intraclass correlation coefficients demonstrated good agreement, with limits of agreement showing accuracy to within 1.2-1.65 g. The wireless accelerometer has scope to be used as a tool to measure peak tibial accelerations during running for the purpose of real-time feedback in gait training systems.